Fe2V4O13 photoanode material: an interesting approach to non-enzymatic glucose oxidation - da Silva Pelissari, Marcelo Rodrigues [UNESP]; Camargo, Luan Pereira; da Silva, Paulo Rogério Catarini; Dall’Antonia, Luiz Henrique (Springer Nature, 2022)
The use of non-enzymatic material for the electrooxidation reaction of glucose is still a challenge to be overcome since these materials must have high sensitivity to glucose, high chemical stability and, if possible, be obtained quickly and with a low-cost process. In this context, iron vanadate (Fe2V4O13) was successfully synthesized using the easy and low-cost Successive Ionic Layer Adsorption and Reaction process and used as an interesting non-enzymatic photoanode material approach for the photoelectrochemical oxidation reaction of glucose. From the X-ray diffraction and Raman measurements, it was possible to observe that the monoclinic crystalline phase Fe2V4O13 was formed at 500 °C, without any secondary phases. The electrochemical characterization, performed by linear sweep voltammetry (LSV), chronoamperometry and electrochemical impedance spectroscopy techniques, under light condition, showed the remarkable photoelectrochemical activity of the FTO/Fe2V4O13 electrode, such as a high photocurrent density at + 0.6 V vs. Ag/AgCl (0.2 mA cm−2); good reproducibility under transient light condition; low charge transfer resistance; and flat band potential consistent with the LSV and typical value of this material (+ 0.45 V). The performance of the electrode as non-enzymatic glucose interaction, carried out by chronoamperometry technique, showed a remarkable performance in the photoelectrooxidation reaction of glucose, with linear behavior (R2 = 0.9975) of the analytical curve (glucose concentration from 0 to 10 mmol L−1), excellent reproducibility, a slight loss in photoelectrochemical signal after five successive reading cycles, good sensitivity (0.370 μA mM−1 cm−2) and limit of detection (52 µmol L–1). Besides, the analysis of interference species showed good electrode selectivity. Graphical abstract: Fe2V2O13 photoelectrode obtained by the Successive Ionic Layer Adsorption and Reaction (SILAR) process, and its use for glucose photoelectrocatalytic oxidation reaction [Figure not available: see fulltext.]